Inhibition of colorectal cancer progression through conformation-specific targeting of ADAM10 metalloprotease - Mashati, Pargol; Sun, Dan; Reino, Eduardo Garcia; Militello, Giuseppe; Gao, Nicholas; Blandino, Jessica A.; Saha, Nayanendu; Nikolov, Dimitar B.; Premsrirut, Prem K. (Frontiers in Oncology, 2026)
IntroductionColorectal cancer (CRC) is the second leading cause of cancer-related deaths worldwide. Current first- and second-line therapies rely on oxaliplatin- or irinotecan-based combination chemotherapies combined with antibody-mediated inhibition of EGFR- or VEGF-dependent signaling, but these regimens are associated with significant side effects that limit long-term use and effectiveness. ADAM10 has emerged as a potential therapeutic target in CRC due to its role in activating oncogenic pathways such as Notch and EGFR; however, prior approaches targeting ADAM10 showed high toxicity. ADAM10 exists in an open, active conformation and a closed, auto-inhibited conformation, with the active form being more prevalent in tumor cells, providing a rationale for conformation-specific targeting.MethodsTo investigate the therapeutic potential of 1H5, cellular viability was assessed using viability assays, and ADAM10 dependency was evaluated by shRNA-mediated knockdown. Modulation of oncogenic signaling pathways and target gene expression was validated by Western blotting and RT-qPCR, while transcriptomic changes were analyzed by bulk RNA sequencing. The effects of 1H5 on cell migration and invasion were assessed using wound-healing and transwell invasion assays, and therapeutic efficacy was evaluated in vivo using xenograft and syngeneic mouse models.ResultsWe show that 1H5 inhibits Notch and EGFR signaling and reduces proliferation of human CRC cell lines. We also found that 1H5 inhibits Wnt/β-catenin signaling in CRC cells and reduces their migration and invasion capacity. Finally, treatment studies in CRC cell line-derived xenograft models revealed marked antitumorigenic properties of 1H5.DiscussionTogether, these findings demonstrate that selective targeting of the active conformation of ADAM10 enables simultaneous inhibition of multiple oncogenic pathways involved in CRC growth and progression and represents a promising therapeutic strategy warranting further clinical evaluation.